B -AND B - COMPLETENESS IN LOCALLY CONVEX ALGEBRAS AND THE E x THEOREM (Journal of Sciences, Islamic Republic of Iran)
Let E be a B-complete (B -complete) locally convex algebra and $ the topological direct sum of countably many copies of the scalar field with a jointly continuous algebra multiplication. It has been shown that E is also B-complete (B -complete) for componentwise multiplication on E . B-and Br-completeness of E , the unitization of E, and also of E x for other multiplications on E has been studied.